CINCIN ARSIP: PENANGGULANGAN BENCANA DAN PENGELOLAAN ARSIP: Array - Raistiwar Pratama (Jurnal Kearsipan, 2019)
Disaster mitigation consists of three sequential processes, similar to functional approach towards disaster. The two puts concern that series system able to capture disaster function each of related governmental bodies. Despite the various structures and names of government bodies, it is their single function that creates records. Function defines activity and transaction. Align to it, life cycle approach is considered fail to capture the series system. Thus, records continuum contemporarily suitable. Preserving collective memory and providing access over time are main requirements. Structurism might lower the tense between structure and function.